Efficiency of Production Factors used in Carrot (Daucus carota) Farming - Suswadi Suswadi; Agung Prasetyo; Dewi Gesang Nurlarasati (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2022)
The farmers' income is uncertain in Boyolali following the unstable weather. This study aims to know the factors that affect the production of carrots and the efficiency level of production factors in carrot farming. The method used in this research was the survey method that was performed in the Argo Ayuningtani Farmer Group, Senden Village, Selo District, Boyolali Regency. The respondent was determined by observation of as many as 30 carrot farmers. The collected data were in the form of primary and secondary data. The primary data were obtained from literature studies and studies of other institutions that related to this research. Data were analyzed using quantitative analysis using the Cobb Douglass model. The results of the study found that several factors that simultaneously affected the productivity of carrot farming were the total area of land (X1), labor (X2), seeds (X3), organic fertilizer (X4), fertilizer Za (X5) used by farmers. The number of seeds is the most influential production factor in the productivity of the Argo Ayuningtani Farmer Group, Senden Village, Selo District, Boyolali Regency.